France - Cohen, Jean Louis (London Reaktion Books, 2015)
Everyone knows Notre Dame, the Eiffel Tower, and the chateaux of the Loire Valley, but French architects have also produced some of the most iconic buildings of the twentieth century, playing a central role in the emergence and development of modernism. In France, Jean-Louis Cohen presents a complete narrative of the unfolding architectural modernity in the country, grappling not only with the buildings but also with the political and critical context surrounding them.
Keywords: ARCHITECTURE BY REGION (AR-REG)